Analysis of quantitative and qualitative parameters influencing the housing planning of the country’s Provinces - malihe Izadi; Hamid reza varesi; Mahmod mahmodzadeh (تحقیقات کاربردی علوم جغرافیایی)
Attention to housing and planning in line with sustainable development in the framework for planning national and regional is to our use of the knowledge and techniques of programming, existing situation and issues related to it is made clear that. To the main goal this research study and the analysis of the most tiresome effective in planning housing classification level and province of the country based on.This is a descriptive method of research-analysis. collecting data with the use of the results of the census and public housing in 1390 and resources library and documents and evidence have been done. The index of the study, 27 indicators inclusive of housing is a little bit you returned home Models based on regional planning(Multi-criteria decision analysis Vikor) Has beenanalyzed. Using a factor analysis technique, These four factors were  total 91/18 % of the variance explained Calculation of productivity. The provinces have indices using vikor. Based on this classification level, Esfahan(Zero coefficient),Golestan(Zero), Tehran(zero), East Azerbaijan(0/079 coefficient) in first to fourth levels are very Brkhordar And Semnan provinces(0/87),Ardabil(0/88), Sistan and Baluchistan(0/90)          ,Bushehr(0/90), Lorestan(0/91), Hormozgan(0/91),Mahal   Bakhtiari (0/92), Kohkiluyeh &Bourahmd(0/94),Qom(0/94),North Khorasan (0/96) and Elam(1), Respectively, and thelastlevelsvery brkhordar havetheleast.